Indigenous youth and multilingualism: Language identity, ideology, and practice in dynamic cultural worlds. (Revista Peruana de Investigación Educativa, 2016)
Wyman, L. T., McCarty, T. L. y Nicholas S. E. (Eds.) (2014).Indigenous youth and multilingualism: Language identity, ideology, and practice in dynamic cultural worlds.New York: Routledge